Djurskydd - Gabrielson, Malin; Madsen, Karin (2005)
The purpose with this thesis was to form an opinion of how the animal welfare in Sweden is experienced by both farmers and animal inspectors. A great part of this work consists of an inquiry concerning the south and the middle of Sweden. We sent the inquiries to milk and meat producers and to animal inspectors. The response was high, which indicates that this is a subject that affects many people. Our literature study is mostly made on the library bases LIBRIS and LUKAS. The facts we found there were directed towards animal experimentation and furred animal breeding. In order to compare with earlier results we used investigations that had been made by Riksrevisionen 2003. There is a difference in opinions about the new Swedish animal welfare agency that started first of January 2004. Some people think it would be better to put the resources on already existing activity instead of starting up a new authority. Others think that it takes a new central authority to get a better animal welfare in Sweden. When you read about animal welfare matters in the daily press it is often angled from different parts. In that way it could be interesting for both parts, to make your own opinion about how it works in practice. In order to limit this thesis we concentrated on milk and beef cows. In the thesis there are parts from the Animal Welfare Act (1988:534) and the Animal Welfare Ordinance. This was to clear out the acts that are questioned by both farmers and animal inspectors in the inquiry. The thesis also contains specification of the animal welfare in Sweden. That includes all the actors that are involved in the animal welfare today, from the Parliament to the Police Authorities. The search for the articles was concentrated on the new Animal Welfare Agency. One of the conclusions is that animal welfare in Sweden is very varying between different districts.